Future perspectives on international criminal justice - Stahn, Carsten; Herik, Larissa J. van den (T.M.C. Asser Press, 2010)
Future perspectives on international criminal justice : through the looking glass / Carsten Stahn & Larissa van den Herik -- Part I. The influence of scholars and practitioners on the development and conceptualization of international criminal law. 'Satires of circumstance' : some notes on war crimes trials and irony / Gerry Simpson ; The banality of evil on trial / Alette Smeulers & Wouter Werner ; Why international criminal lawyers should read Mirjan Damaška / Harmen van der Wilt ; The gentle humanizer of humanitarian law : Antonio Cassese and the creation of the customary law of non-international armed conflict / Tamàs Hoffmann ; The international criminal legal process : towards a realistic model of international criminal law in action / Christoph Burchard -- Part II. Theorizing international criminal justice. The two liberalisms of international criminal law / Darryl Robinson ; International criminal law at the crossroads : from ad hoc imposition to a treaty-based universal system / Kai Ambos ; In search of the 'vertical' : towards an institutional theory of international criminal justice's core / Frédéric Mégret -- Part III. Re-assessing the balance between international and domestic jurisdiction. Situational gravity under the Rome Statute / Kevin Jon Heller ; When law 'expresses' more than it cares to admit : comments on Heller / Mark Osiel ; Should the prosecution of ordinary crimes in domestic jurisdictions satisfy the complementarity principle? / Dawn Sedman ; Interpreting complementarity and interests of justice in the presence of restorative-based alternative forms of justice / Marta Valiñas ; Universal jurisdiction and the prosecution of excluded asylum seekers / Elizabeth Santalla --